Intraspecific Variability in Seed Quality of Native Tree Species in Mountain Forests in Southern Ecuador: Implications for Forest Restoration - Palomeque, Ximena (2017)
One of the most important aspects in efficient plant production for restoration purposes is seed quality and its variability. The main goal of this study was to evaluate seed parameters according to the rules of “International Seed Testing Association” among different mother trees or individuals of seven native tree species (Cedrela montana, Morella pubescens, Inga acreana, Tabebuia chrysantha, Ocotea heterochroma, Oreocallis grandiflora and Myrcianthes rhopaloides) in two mountain forests in the Southern of Ecuador. These species were selected based on the ecological, socioeconomic importance, and their high potential for restoration. From a total of 35 mother trees for all species, seeds were collected in their fructification periods, and in the laboratory the following seed parameters were analyzed: purity, seed weight, moisture content, and germination; in addition, the coefficient of velocity of germination was determined as well. The results showed an intraspecific similarity in each species for the majority of seed parameters. However, the seed weight showed a high intraspecific variability for all species. The germination parameter showed differences among individuals for C. montana, T. chrysantha, O. heterochroma and M. rophaloides. In regard to the coefficient of velocity of germination, individual of species such as O. grandiflora and I. acreana showed a high coefficient in contrast to the individuals of O. heterochroma and M. pubescens. The information generated in this study could be a first step in the formulation of guidelines for the mass plant production for restoration purposes.